Energy hedging in business and its implications for business planning - Pavlov, Tomáš (2024)
This Master's thesis explores the importance of energy hedging and its implications for business planning. The study aims to identify the most effective strategies for hedging natural gas prices in the Czech market, examining various financial instruments such as futures, swaps, forwards, and options. Through an extensive literature review and empirical analysis, three primary research questions are addressed: the benefits of energy hedging with standardized derivatives compared to standard contractual agreements, the impact of margin calls on cash flow planning, and the influence of margin calls on interest expenses. The research utilizes historical data and models to test hypotheses, revealing that long-term futures contracts consistently outperform fixed-price contracts. The findings suggest that adopting effective hedging strategies can significantly enhance business stability and financial performance by mitigating price risks and improving cash flow management.